DESIGNING BATIK WITH THE SOURCE OF SOLO ARCHITECTURAL IDEAS FOR OUTERWEAR PRODUCTS - Salsabila, Azka; Santoso, Ratna Endah (Arty: Jurnal Seni Rupa, 2021)
This design was carried out as a form of batik motif development by making Solo city architecture a source of visual ideas, given the diverse architectural heritage cities in Solo that can be used as a source of ideas. The purpose of this design is to produce batik products by exploring the visual of Solo city architecture into batik motifs to be developed towards new, more innovative designs. The design stage includes (1) observing and looking for data on batik and the architecture of the city of Solo, (2) conducting visual exploration, and (3) conducting trials on the source of the ideas taken, namely the architecture of the city of Solo. The results of this batik design are as follows: (1) This design results in a renewal of the motif design that displays the visuals of Solo City Architecture which previously was rarely applied as a batik motif. The results of this development succeeded in making 8 designs with visuals of Solo City Architecture that were processed using the Distortion style. (2) This design is applied as outerwear for women with a age range of 24-30 years. Design development considerations are adjusted to the age range and consumer tastes.